Neuromuscular and performance responses to resisted sprint loads in elite female sprinters - Bartosz-Jeffries, M.; Loturco, I.; Zajac, A.; Maszczyk, A.; Freitas, T. T.; Alcaraz, P. E.; Pereira, L. A.; Golas, A. (Sports, 2025)
This study examined the effects of motorized resisted sprint training (RST) on neuromuscular activation and sprint performance in elite female sprinters. Ten highly trained athletes (age: 23 ± 2.8 years; body mass: 58.3 ± 4.7 kg) performed two maximal 30 m unresisted sprints and six resisted sprints under three different load conditions (i.e., 5%, 10%, and 15% of body mass [BM]), randomized in a counterbalanced design. Surface electromyography (EMG) of eight lower-limb muscles was recorded bilaterally using wearable EMG-integrated shorts. Sprint times were captured using dual-beam photocells, and motorized resistance was applied with the SPRINT 1080 device. Repeated-measures ANOVA revealed a significant load-dependent effect on sprint time (p < 0.001, n2 = 0.926), with performance decreasing as resistance increased. However, no significant changes were observed in most muscle groups across load conditions, except for a non-significant trend toward increased left gluteus maximus activity (p = 0.053, n2 = 0.136). Interestingly, greater inter-individual variability in both sprint performance and muscle activation was observed as external loads increased. These findings suggest that elite female sprinters maintain highly stable neuromuscular recruitment patterns, particularly in the quadriceps and hamstrings, when sprinting with external loads up to 15% BM, potentially reflecting a ceiling effect in their neuromuscular responsiveness. From a practical perspective, light-to-moderate RST may effectively stimulate posterior chain muscles without disrupting sprinting mechanics. Future longitudinal studies are warranted to explore the chronic adaptations to motorized RST and to determine whether the observed neuromuscular strategies are consistent across sexes.